Winged Shepherdess - DelVecchio, Rosa Maria (Cornfield Review, 2013)
"Winged Shepherdess" is a poem about an elderly woman who, through her perceptions of a spiritual image from her childhood days, finds freedom from the confines of her wheelchair.